Attenção!!! Vende-se saúde: tradições discursivas em anúncios sobre medicamentos nos jornais paraibanos dos século XIX - Lima., Isabella Cristina Amorim de Lucena (2013)
This study aims to identify and analyze the discursive traditions presented in medicine advertisements from some Paraiba s newspapers of the nineteenth century, emphasizing the importance of socio-historical and economic context at that specific time. For this purpose, we used the Traditional Discourse Theoriescreated developed by Coseriu s ideas (1979), which served as the basis for the development of researches from other authors, such as Koch (1997), Oesterreicher (1999), Kabatek and Utterance Theory (Bakhtin, 1992 [1979]), observing the dialogical nature of language in this genre of discourse, characterizing it and checking its historical evolution through the time. The corpus collected belongs to the book " Quem o pretender comprar dirija-se a... , " by Aldrigue and Nicolau (2009) and the newspapers: Jornal O Publicador (1862), Jornal da Parahyba (1875 ), Jornal O Mercantil (1883 and 1884), Jornal O Estado da Parahyba (1891), Jornal O Parahybano (1892) and Jornal A União (1893). The analysis revealed that, although great changes have occurred between the XIX and XXI centuries, some linguistics features related to advertising remained, such as the communication between the newspaper advertisement technical language with adjectives and adverbs. Besides it, we found out the recurring presence of the categories that refer to the reference to authority, to drug indications, dosage and mode of use, the composition of the product and its presentation and about the establishment trade in which the product is sold. In contrast to it, we detected some changes in the advertisements lexical and structural compositions due the technological creations in this area and also the infinite textual media that we are daily exposed.